2014
DOI: 10.1063/1.4886555
|View full text |Cite
|
Sign up to set email alerts
|

Research Update: Retardation and acceleration of phase separation evaluated from observation of imbalance between structure and valence in LiFePO4/FePO4 electrode

Abstract: LiFePO4 is a potential positive electrode material for lithium ion batteries. We have experimentally observed an imbalance between the valence change of Fe ions and the structure change from the LiFePO4 phase to the FePO4 phase during delithiation by simultaneous in situ XRD and XANES measurements in an LiFePO4/FePO4 electrode. The ratio of structure change to valence change clearly indicates that the phase separation from LiFePO4 to FePO4 is suppressed at the beginning of delithiation, while it is accelerated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…It is obvious that the MP unit cell experiences a volume expansion of about 6% after the insertion of 1 mole of Li. This value is close to that of FePO 4 after 1 mole Li insertion, that is, in the range of 5–8%. , …”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…It is obvious that the MP unit cell experiences a volume expansion of about 6% after the insertion of 1 mole of Li. This value is close to that of FePO 4 after 1 mole Li insertion, that is, in the range of 5–8%. , …”
Section: Resultssupporting
confidence: 81%
“…This value is close to that of FePO 4 after 1 mole Li insertion, that is, in the range of 5−8%. 54,55 Figure 1c,d shows the relaxed structures of LMNP and Mn 0. The reduced unit cell in LMP and MnPO 4 after the Ni substitution can be attributed to the smaller ionic radius of Ni 2+ (0.83 Å), as predicted from Vegard's law.…”
Section: Resultsmentioning
confidence: 99%
“…By using the in situ XRD measurement and the Rietveld refinement, Wang et al investigated the delayed phase transition of submicron LiFePO 4 particles at the rate of 0.1 C, which was possibly originated from the nucleation and growth mechanisms of a new phase. By combining in situ XRD and the X-ray absorption near edge structure, Tokuda et al observed that the phase transition of the LiFePO 4 particle with an equivalent diameter of 177 nm was later than the valence change of Fe ions at the rate of 1 C, owing to the coherent strain caused by the lattice mismatch between two phases. By using in situ XRD and Gaussian curve fitting, Siddique et al revealed that the phase transformation was delayed more seriously at a higher rate which might come from the insufficient Li-ion supply caused by the obstacle of diffusion through the complicated porous network or limited local electronic conductivity.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The P-DAFS measurements were conducted at beamline BL28XU, 29,30 SPring-8, Japan. We used a Si(111) channel-cut monochromator with a 3 mm gap in combination with two pairs of horizontal and vertical Rh-coated mirrors upstream and downstream of the monochromator to eliminate highorder harmonics.…”
Section: P-dafs Measurements and Analysismentioning
confidence: 99%